1962
DOI: 10.1111/j.1096-3642.1962.tb01626.x
|View full text |Cite
|
Sign up to set email alerts
|

Filter-feeding mechanisms in some brachiopods from New Zealand

Abstract: Summary All major types of lophophore in branehiopods, except the ptyeholophe, are represented among the growth stages of the five species described here. The basic ciliary mechanisms are uniform, and similar to those known in other species. The mantle cavity is always divided by the lophophore into inhalant and exhalant chambers with separate apertures; but the arrangement may change radically during ontogeny with the increasing complexity of the lophophore, which is attributed to a dimensional relation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
1

Year Published

1962
1962
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 21 publications
1
78
0
1
Order By: Relevance
“…In the one type particles rent diameter. Middle, earliest functional lophophore stage; left, short segment of lophophore with filaments; right, cross section of filament, indicating path of particle from through current into surface current (modified from Rudwick, 1962Rudwick, , 1970. (C) Bivalve, upstream retention.…”
Section: Resultsmentioning
confidence: 99%
“…In the one type particles rent diameter. Middle, earliest functional lophophore stage; left, short segment of lophophore with filaments; right, cross section of filament, indicating path of particle from through current into surface current (modified from Rudwick, 1962Rudwick, , 1970. (C) Bivalve, upstream retention.…”
Section: Resultsmentioning
confidence: 99%
“…3. Rowell (1961) has suggested that the inarticulate Discinisca may be a living representative of a type of spirolophous current-system postulated by Rudwick (1960) for the extinct Spiriferoidea, in which the interior of the spirals would be filled with exhalant water, the direction of filtration being reversed from that found in Crania, Lingula and Tegulorhynchia. Should this be confirmed by observation on living specimens, it will add support to the theory of an inherent limitation on the possible variety of spirolophous current-systems.…”
Section: The Current-systemmentioning
confidence: 99%
“…The current-system (Rudwick, 1960) of C. anomala, like that of all other brachiopods that have been investigated, consists essentially of one-way flow through a mantle cavity which is completely divided by the lophophore into separate inhalant and exhalant chambers, with separate inhalant and exhalant apertures to the exterior.…”
Section: The Current-systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Long (1964) dealt mainly with l'arval development, and reviews of the phylum by Hyman (1959) and Rudwick (1970) confirmed that little is known about breeding seasons, the varialbles influencing gonad ripening, or the mechanisms which trigger spawning. Water tempemture, day lenglth, and other physical variables governed by latitude are known to influence the breeding cycle in many invertebrates (see, for example, Thorson (1950) and Giese (1959», and the same can be expected in brachiopods (Rudwick 1962, Doherty 1976). …”
Section: Introductionmentioning
confidence: 99%